Wasiat Wajibah Bagi Ahli Waris Beda Agama (Analisis Terhadap Putusan Mahkamah Agung Nomor: 368K/AG/1995) - mutmainah, iin; Sabir, Muhammad (DIKTUM: Jurnal Syariah dan Hukum, 2019)
This study discusses about the testament wajibah to differently religious heirs (an Analysis of Supreme Court decision number: 368 K/AG/1995). The purpose of this study are to know about the principle of inheritance under islamic law, and to understand the status of testament to differently religious heirs , and to analyze the constitute of consideration and the legal basis used in deciding the rights of differently religious heirs. The result show that the testament wajibah given to differently religious heirs become a problem because of the status of differently religion, these heirs cannot get inheritance rights. Through the decision of supreme court, judge ruled that differently religious heirs have the right to get inheritance with some consideration. Although there is no rule on testament wajibah to differently religious heirs, the judge have succeeded in ijtihad, finding and exploring the value of existing law. This decree shows that the judges actually carry out duties as a legislator who receive, examine, and decide cases such a new through benefit consideration based on the Qur’an and Hadith